DIKIRI POL: FALLACIES, FACTS AND THE FUTURE - R.R.A. Peries (International Coconut Community, 1995)
The occurrenee of a dikiri type endospenn the porapol and kamandala forms of the vatiety (Typica), has led to the advancement of the hypothesis that dikiri is not a form of coconut with in the Typica vadety, but merely a kernel type, which can occur in any tall form of coconut. The argumentis also made that from an evolutionary point of view, the daid kernel is the manifestation for an undesirable allele, which has been made use of by man for his advantage. A review of the literature examines the mechanism of occurrenee of the dikiri charader and the explanation offered on the aberrant condition of the dikiri kernel.